2009
DOI: 10.1111/j.1939-1676.2008.0253.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parenteral Selenium Administration to Sheep on Prevalence and Recovery from Footrot

Abstract: Background: Insufficient intake of selenium (Se) is common in many regions, and can contribute to increased susceptibility to and prolonged recovery from infectious diseases.Objective: To determine the effect of Se administration in decreasing the severity and prevalence of footrot in sheep. Animals: Thirty-eight footrot-affected and 19 nonaffected sheep from a commercial flock of known high incidence of footrot.Methods: Placebo-controlled, prospective, 15-month clinical trial. Footrot-affected sheep were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…Selenium is an essential element in ruminant's diet which provides a significant source of antioxidant defence and plays an important role in optimising both the immune response and disease resistance (Spears and Weiss, 2008). Indeed, it has been demonstrated that footrot affected sheep have lower blood selenium concentration and that selenium supplementation resulted in a more rapid improvement of foot lesions (Hall et al, 2009). Albumin is a free radical scavenger but it is also the predominant oxidised protein contributing to AOPP formation (Celi, 2011b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Selenium is an essential element in ruminant's diet which provides a significant source of antioxidant defence and plays an important role in optimising both the immune response and disease resistance (Spears and Weiss, 2008). Indeed, it has been demonstrated that footrot affected sheep have lower blood selenium concentration and that selenium supplementation resulted in a more rapid improvement of foot lesions (Hall et al, 2009). Albumin is a free radical scavenger but it is also the predominant oxidised protein contributing to AOPP formation (Celi, 2011b).…”
Section: Discussionmentioning
confidence: 98%
“…Selenium is an essential element in the diet of animals and is important in host antioxidant defense (Rivera et al, 2005). Recently, it has been shown that whole-blood selenium is decreased in footrot-affected sheep and that parenteral selenium supplementation accelerates recovery from footrot (Hall et al, 2009). Therefore, it seems that footrot could induce oxidative stress, leading to increase in formation of free radicals.…”
Section: Introductionmentioning
confidence: 98%
“…The second pattern develops after birth in lambs within 3-6 weeks of birth but may occur as late as 4 months after birth [5]. The importance and roles of Se, selenoproteins, and vit E in muscle function and other veterinary important viewpoints were presented [5][6][7][8][9]. However, beneficial effects of nutritional or parenteral administration of vit E and Se have not been universal among studies [10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…We reported previously that FR-affected sheep have lower whole-blood selenium (WB-Se) concentrations and that parenteral Se-supplementation in conjunction with routine control practices accelerates recovery from FR [12]. As a follow-up, we examined in this study the mechanisms by which Se may facilitate recovery from FR.…”
Section: Introductionmentioning
confidence: 99%